증기 메탄 개질 반응의 Ru 촉매 Kinetic Parameter 예측 - 주종효(CHONGHYO JOO); 김명준(MYUNGJUN KIM); 조형태(HYUNGTAE CHO); 이재원(JAEWON LEE); 김정환(JUNGHWAN KIM) (한국수소 및 신에너지학회 논문집, 2022)
This study proposes kinetic parameters of Ru catalyst for steam methane reforming (SMR). First, extensive experiments are performed under different SMR conditions to evaluate performance of the catalyst in SMR. Second, a kinetic model is designed and developed for parameter estimation and validation using gPROMS. Finally, estimated parameters are fitted to the kinetic model and then, the model results are compared with the experimental data. The model results are in a good agreement with the experimental data.